Fundamentals of innovation in modern banking services - Nizami Khudiyev; Ragib Mammadli (Agora International Journal of Economical Sciences (AIJES), 2025)
In today's constantly evolving technological world, banks need to implement modern innovations to remain competitive in banking environment and meet the growing needs of their customers. Innovative advancements help banks digitize their banking services, operations and management, improve efficiency, productivity and functionality, reduce costs, create new banking products and improve existing ones. In addition to their countless benefits, innovations also create numerous potential risks and challenges for banks.Using a mixed research methodology, this article examines the main types of innovation implemented by banks in banking services and management, highlights their main characteristics and analyzes their common benefits and challenges. Demographic analysis part of the article explores the number of users of digital banking services worldwide and the factors influencing their adoption of modern innovations. Based on the findings of this article, the conclusion part offers brief recommendations to banks for the effective implementation of modern innovations and maximizing their benefits.
Keywords: 330; banking innovation; innovative banking services; incremental innovation; disruptive innovation; substantive innovation